Pengaruh tinggi pemotongan berbeda terhadap kandungan serat kasar dan protein kasar serta mineral kalsium (ca) rumput setaria (Setaria sphacelata) - Dewi Narayani; Herayanti Panca Nastiti; Dominggus B. Osa (Jurnal Peternakan Lahan Kering, 2019)
The purpose of this study was to determine the content of crude fiber, crude protein and minerals calcium (Ca) of Setaria grass at the firts harvest that cut with the to different defoliation intensity. The method used is an experimental method using a Completely Randomized Design (CRD) consisting of the 3 treatments and 5 replications. The treatment tested in this study is Ta = defoliation intensity 5cm, Tb = defoliation intensity 10cm, Tc = defoliation intensity 15cm. The results showed that of Analysis of Variance (Anova) indicate that the treatment had very significant effect (P<0.01) on crude fiber and crude protein content and had a significant effect (P<0.05) on calcium (Ca) minerals on the Setaria grass. The results from the test of Duncan further found that the content of crude fiber of Setaria sphacelata grass between Ta : Tb treatments different significantly (P<0,01), the treatment between Ta : Tc was very different (P<0.01) while the inter-treatment Tb : Tc was not different significantly (P>0.05), crude protein content of Setaria sphacelata grass between treatments of Tb : Ta was significantly different (P<0,01), inter-treatment of Tb : Tc had significant differences (P<0,05) and the treatment between Tc : Ta was not significantly different (P>0,05) and the mineral content of Setaria sphacelata calcium (Ca) grass between Ta : Tb treatments was significantly differents (P<0,05), the treatment between Ta : Tc had not significant differences (P>0,05) and the different from defoliation treatment between Tc : Tb was not significant (P>0,05). the conclusion was that defoliation intensity of 15cm on Setaria grass produced the best quality with Crude Protein content (9,48%), Crude Fiber content (26,55%) and Mineral Calcium content (0,096%).